Efficacy of an individualized social competence training for children with Oppositional Defiant Disorders/Conduct Disorders. (4th May 2017) - Goertz-Dorten, Anja; Benesch, Christina; Hautmann, Christopher; Berk-Pawlitzek, Emel; Faber, Martin; Lindenschmidt, Timo; Stadermann, Rahel; Schuh, Lioba; Doepfner, Manfred
Abstract: Objectives: Group-based Cognitive–Behavioral Therapy of children with aggressive behavior has resulted in significant reductions of behavior problems with small to medium effect sizes. We report the efficacy of an individualized Treatment Program for Children with Aggressive Behavior.Method: A within-subject design with two phases (waiting, treatment) was chosen. Sixty boys aged 6–12 years with peer-related aggressive behavior were included. The course of the outcome measures (growth rates) during a 6-week waiting phase was compared with those in the subsequent treatment phase (24 weekly child sessions together with an average of 8 parent contacts) by multilevel modeling. Primary outcome was peer-related aggressive behavior rated by parents. Further outcome measures included parent ratings and patient self-reports of aggressive and prosocial behavior.Results: During the treatment, growth rates for all parent-rated outcome measures were significant ( p < .001) and comparison with the waiting phase indicated a stronger decrease in aggressive behavior and a stronger increase in prosocial behavior. For all self-rated outcome measures, growth rates during the treatment were significant ( p < .01), but comparison with the waiting phase indicated a stronger decrease only for disturbance of social interaction.Conclusions: The treatment program is an effective intervention for children with peer-related aggressive behavior.